2005
DOI: 10.1055/s-2004-830541
|View full text |Cite
|
Sign up to set email alerts
|

Subclinical Hyperthyroidism in Patients with Nodular Goiter Represents a Hypermetabolic State

Abstract: The aim of the study was to examine the metabolic status in patients with suppressed TSH but values of FT4I and T3 within the reference range (subclinical hyperthyroidism [sH]). Thirteen patients and 13 control persons with nodular goiter were included. The metabolic state was determined by measurements of basal oxygen consumption (VO2), bone mineral density (BMD), and the circadian variation of TSH. Further was the pituitary thyroid axis examined by studying the effect of lowering thyroid hormones by methimaz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
2

Year Published

2005
2005
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 14 publications
1
3
2
Order By: Relevance
“…This is corroborated by the observation, that VO 2 correlate with T 3 , indicating that T 3 or a deiodination product of T 3 (T 2 ) stimulates oxygen consumption at the mitochondrial level within hours. We have previously demonstrated a correlation between TSH and VO 2 in euthyroid subjects [13] and in patients with subclinical hyperthyroidism [14] , but it was not possible to demonstrate a significant correlation between VO 2 and TSH in persons with subclinical hypothyroidism in the present study. An explanation may be that the feedback from the thyrotrope cells in the pituitary may be impaired in the present condition corresponding to a decreased pituitary D 2 activity as previously described [12] .…”
Section: Discussion ▼contrasting
confidence: 88%
“…This is corroborated by the observation, that VO 2 correlate with T 3 , indicating that T 3 or a deiodination product of T 3 (T 2 ) stimulates oxygen consumption at the mitochondrial level within hours. We have previously demonstrated a correlation between TSH and VO 2 in euthyroid subjects [13] and in patients with subclinical hyperthyroidism [14] , but it was not possible to demonstrate a significant correlation between VO 2 and TSH in persons with subclinical hypothyroidism in the present study. An explanation may be that the feedback from the thyrotrope cells in the pituitary may be impaired in the present condition corresponding to a decreased pituitary D 2 activity as previously described [12] .…”
Section: Discussion ▼contrasting
confidence: 88%
“…These data are in contrast to studies in endogenous subclinical hyperthyroidism, which have reported increased basal VO 2 , decreased lean body mass, and increased percent body fat (17)(18)(19). Subjects in one study were given methimazole, and basal VO 2 normalized when they became euthyroid (17).…”
Section: Discussioncontrasting
confidence: 50%
“…Subjects in one study were given methimazole, and basal VO 2 normalized when they became euthyroid (17). These studies suggest that endogenous Values shown are mean -standard error of the mean, unless otherwise indicated.…”
Section: Discussionmentioning
confidence: 98%
“…Women older than 65 years of age who have suppressed TSH have been reported to have a threefold increased risk for hip fractures and a fourfold increased risk for vertebral fracture [41]. Decreased BMD was observed in a small group of patients with subclinical hyperthyroidism with nodular goiter [50]. Similar data have been reported in preand postmenopausal women with subclinical hyperthyroidism caused by multinodular goiter.…”
Section: Endogenous Subclinical Hyperthyroidismsupporting
confidence: 58%